Identification of a novel aminoglycoside nucleotidyltransferase ANT(3″)-Ic from Citrobacter telavivum S24 - Junwan Lu; Mei Zhu; Jingzeng Ye; Leyao Xu; Chunhan Song; Kewei Li; Qiyu Bao; Xi Lin (BMC Microbiology)
Abstract Understanding the antibiotic resistance profile of the emerging pathogen Citrobacter telavivum S24 is important for clinical care, surveillance, and research. C. telavivum S24, a strain that exhibits resistance to both streptomycin and spectinomycin, was isolated from the soil at a broiler chicken farm. The strain was identified by whole-genome sequencing and average nucleotide identity analyses. Annotation of the resistance genes revealed that a novel aminoglycoside resistance gene, designated ant(3″)-Ic, is located on the chromosome of C. telavivum S24. This gene exhibits 52% similarity with the previously functionally characterized resistance gene aadA23. It distinguishes itself from ant(3″)-Ia and ant(3″)-Ib genes, and represents an independent branch. The ant(3″)-Ic gene is recognized as an inherent resistance gene of C. telavivum within a conserved genetic environment. The product of the ant(3″)-Ic gene is the aminoglycoside nucleotidyltransferase ANT(3″)-Ic, which has a theoretical pI of 5.05 and a molecular mass of 29 kDa. ANT(3”)-Ic inactivates streptomycin and spectinomycin with the K m of 46.13 and 115.90 µM, respectively. The discovery of the novel antibiotic resistance gene ant(3″)-Ic and the functional characterization of ANT(3”)-Ic will facilitate more targeted surveillance and treatment strategies for preventing and controlling zoonotic pathogens of zoonotic diseases.